MIXED MEDIA SEBAGAI ALTERNATIF PENCIPTAAN LUKISAN DI MUSEUM RUDY ISBANDI SURABAYA - Suhendroyono, Suhendroyono; Nugraheni, Novita (Kepariwisataan: Jurnal Ilmiah, 2016)
Mixed Media developments in the manufacture of paintings at the Museum Rudy Isbandi has evolved with new innovations to be able to attract the attention of visitors. Utilization of used goods for Mixed Media painting techniques as an alternative of making the painting a positive impact on the environment even though not all of the junk could dimanfaatakn to be a painting that transform media and creative. The use of second-hand goods can produce works of art that manifold visual and 3-dimensional character who is able to make the artists are interested in collecting. The facilities provided by the Museum Rudy Isbandi not been standardized to make visitors comfortable. Keywords: Rudy Isbndi Museum, Development of Mixed Media, Utilization of thrift, appeal used goods